Euterpe oleracea fruit (Açai)-enriched diet suppresses the development of experimental cerebral malaria induced by Plasmodium berghei (ANKA) infection - Karen Renata Herculano Matos Oliveira; Marjorie Lujan Marques Torres; Nayara Kauffmann; Brenda Jaqueline de Azevedo Ataíde; Nívia de Souza Franco Mendes; Larissa Medeiros dos Anjos; Rosivaldo dos Santos Borges; Carlomagno Pacheco Bahia; Luana Ketlen Reis Leão; Adelaide da Conceição Fonseca Passos; Anderson Manoel Herculano; Evander de Jesus Oliveira Batista (BMC, 2022)
Abstract Background Cerebral malaria is one of the most severe complications attributed to protozoal infection by Plasmodium falciparum, gaining prominence in children mortality rates in endemic areas. This condition has a complex pathogenesis associated with behavioral, cognitive and motor sequels in humans and current antimalarial therapies have shown little effect in those aspects. Natural products with antioxidant and anti-inflammatory properties have become a valuable alternative therapeutic option in the treatment of distinct conditions. In this context, this study investigated the neuroprotective effect of Euterpe oleracea (açai) enriched diet during the development of experimental cerebral malaria induced by the inoculation of Swiss albino mice with Plasmodium berghei ANKA strain. Methods After Plasmodium infection, animals were maintained on a feeding with Euterpe oleracea enriched ration and parameters such as survival curve, parasitemia and body weight were routinely monitored. The present study has also evaluated the effect of açai-enriched diet on the blood-brain barrier leakage, histological alterations and neurocognitive impairments in mice developing cerebral malaria. Results Our results demonstrate that between 7th-19th day post infection the survival rate of the group treated with açai enriched ration was higher when compared with Plasmodium-infected mice in which 100% of mice died until the 11th days post-infection, demonstrating that açai diet has a protective effect on the survival of infected treated animals. The same was observed in the brain vascular extravasation, where Evans blue dye assays showed significantly less dye extravasation in the brains of Plasmodium-infected mice treated with açai enriched ration, demonstrating more preserved blood-brain barrier integrity. Açai-enriched diet also attenuate the histopathological alterations elicited by Plasmodium berghei infection. We also showed a decrease of the neurological impairments arising from the exposure of cerebral parenchyma in the group treated with açai diet, ameliorating motor and neuropsychiatric changes, analyzed through the SHIRPA protocol. Conclusion With these results, we conclude that the treatment with açai enriched ration decreased the mortality of infected animals, as well as protected the blood-brain barrier and the neurocognitive deficits in Plasmodium-infected animals.